Potential use of telemedicine in paediatrics: a single-centre retrospective review - Zenaz Zarir Sarkari; Corey Fish (BMJ Publishing Group, 2023)
Recent advancements and adoption of telemedicine have affected all aspects of healthcare including paediatrics. While telemedicine has the potential to increase access to paediatric care, the limitations of this service in its current iteration bring into question its usefulness for direct replacement of in-person care, particularly in an acute or urgent care setting. This retrospective review demonstrates that only a small percentage of in-person visits to our practice would have resulted in definitive diagnosis and treatment if facilitated via telemedicine. There is a need for better and more widespread data collection techniques and tools suitable for paediatric remote care implementation before telemedicine becomes a useful diagnostic and treatment tool in an acute or urgent care setting.